Evaluating the risk of cloud computing implementation in PTAR using cloud decision framework by Microsoft / Mohammad Hilmi Haliludin - Haliludin, Mohammad Hilmi (2014)
Cloud computing technology can be defined as one of the new generation in Information technology for organization that provides an easy and affordable technological application and services. Due to the growing needs for information technology (IT) and the current dropping global financial stability, many higher education institutes including universities, are facing problems in providing the essentials of IT supports for administrative, educational, and research activities. This research thus aims to discover the risk of implementing Cloud in Perpustakaan Tun Abdul Razak. The method for this research was a semi-structured interview was being conducted in order to collect data and were chosen PTAR ICT staffs, and UiTM InfoTech staff in UiTM. The data were analyzed qualitatively. The results of this study shows the current of IT infrastructure in PTAR need take a lot of consideration in implementing the Cloud computing. Besides that, the selection of service provider also is one of the important part. At the end, researcher provide the recommendation for PTAR in order to reduce the risk in implementing the Cloud computing.